The Effect of Biology Teaching Materials on the Academic Performance of Senior Secondary School Students in Ilorin West, Ilorin, Kwara State - Abidoye, Florence Omosholape; Abidoye , A. Adekunle; Olaide, Malik S. (International Journal of Educational Innovation and Research, 2023)
This study examined the impact of Biology instructional materials on the academic performance of senior secondary school students in Ilorin West LGA, Kwara State, Nigeria. It employed a descriptive survey research design and targeted Biology students in senior secondary schools. A random sampling technique was used to select 120 students. Data was collected using a questionnaire and analyzed using frequency count, percentage, mean, standard deviation, independent t-test, and ANOVA. The findings revealed a significant positive effect of Biology instructional materials on students' academic performance. Students taught with these materials outperformed those without them. However, no significant differences were found based on gender and class size. The study also highlighted the importance of school type, showing a substantial influence of Biology instructional materials on academic performance. Recommendations include the Ministry of Education providing instructional materials, Biology teachers incorporating them in lessons to foster competition, government support for public schools in obtaining instructional materials, and additional infrastructure like classrooms and laboratories..